2018
DOI: 10.1016/j.jmbbm.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic crack initiation and propagation in crosslinked UHMWPE from clinically relevant notches up to 0.5 mm radius

Abstract: Highly crosslinked UHMWPE is now the material of choice for hard-on-soft bearing couples in total joint replacements. However, the fracture resistance of the polymer remains a design concern for increased longevity of the components in vivo. Fracture research utilizing the traditional linear elastic fracture mechanics (LEFM) or elastic plastic fracture mechanics (EPFM) approach has not yielded a definite failure criterion for UHMWPE. Therefore, an advanced viscous fracture model has been applied to various not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…In a previous study by the authors, a power law relation was obtained between crack initiation time and applied static load for crosslinked UHMWPE [35]. A similar relationship was postulated in this study between cyclic crack initiation time (obtained through video observation of the notch surface) and test frequency (eq.…”
Section: Methodssupporting
confidence: 83%
See 3 more Smart Citations
“…In a previous study by the authors, a power law relation was obtained between crack initiation time and applied static load for crosslinked UHMWPE [35]. A similar relationship was postulated in this study between cyclic crack initiation time (obtained through video observation of the notch surface) and test frequency (eq.…”
Section: Methodssupporting
confidence: 83%
“…The findings for crosslinked UHMWPE [27], as well as findings for non-crosslinked UHMWPE [33] support that static creep loading is a dominant mechanism for crack propagation in crosslinked UHMWPE. As a result of this finding, previous studies by the authors [34,35] focused on the role of static creep loading on determining crack initiation time and crack propagation velocity from a notch in crosslinked UHMWPE. It was found that the Williams' viscous fracture model [36] was able to predict both crack initiation and propagation velocity from a notch in two crosslinked UHMWPE formulations.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Crosslinking of UHMWPE significantly improves wear performance [37][38][39][40], which can be achieved through the use of a silane [41,42], or chemical methods using peroxides [38,43] and irradiation [44][45][46]. The free radicals produced by these methods create the inter-chain covalent bonds, leading to the formation of crosslinking.…”
Section: Irradiationmentioning
confidence: 99%